Guts [compact disc] - Rodrigo, Olivia (Geffen Records, 2023)
Three-time Grammy Award winner Olivia Rodrigo is back with the follow up to her smash hit debut album, SOUR. This album sees her exploring changes in her life. Includes the single Vampire.